1966
DOI: 10.1029/jz071i020p04711
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of stepped and dart leaders in cloud-to-ground lightning strokes

Abstract: Recent observations indicate the rather complete neutralization of volume space charges by induced positive corona streamers. New photographic observations of high‐tension power lines in rain and snow storms reveal strong and heavily branched corona streamers from such hydrometeors. A study of uniform field streamer breakdown in midgap in clean gases, just published, has provided additional information essential to the delineation of the processes active in the forging of the channel of the cloud‐to‐ground str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0
2

Year Published

1982
1982
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 20 publications
5
59
0
2
Order By: Relevance
“…These effects are likely to result in a significant enhancement of the electric field near the ice crystal extremities that, in certain cases, may be sufficient to support corona discharges including positive streamers. Loeb (1966) first suggested that hydrometeor-triggered positive streamer systems could effectively 'funnel' space charge, concentrating it at the origin of the positive streamer system such that the resultant local electric-field enhancements might support the formation of a negative stepped leader. The idea of local electric-field enhancement by positive streamer systems was further explored by Griffiths and Phelps (1976) by means of a model investigation, leading to the conclusion that a small number (usually less than ten) of successive intensifying positive streamer systems, each initiated by individual positive streamers and developing in the same volume as previous streamer systems, could lead to a significant electric-field enhancement at their collective origin.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are likely to result in a significant enhancement of the electric field near the ice crystal extremities that, in certain cases, may be sufficient to support corona discharges including positive streamers. Loeb (1966) first suggested that hydrometeor-triggered positive streamer systems could effectively 'funnel' space charge, concentrating it at the origin of the positive streamer system such that the resultant local electric-field enhancements might support the formation of a negative stepped leader. The idea of local electric-field enhancement by positive streamer systems was further explored by Griffiths and Phelps (1976) by means of a model investigation, leading to the conclusion that a small number (usually less than ten) of successive intensifying positive streamer systems, each initiated by individual positive streamers and developing in the same volume as previous streamer systems, could lead to a significant electric-field enhancement at their collective origin.…”
Section: Introductionmentioning
confidence: 99%
“…With reference to the best known category, the cloud-to-ground lightning, the main stages are essentially the preliminary breakdown, the stepped leader, the connecting leader and the return stroke, however subsequent stages may also occur (Volland, 1984;Uman, 1987). This study deals with the macroscopic development of the stepped leader channel (Uman, 1987;Golde, 1977;Chalmers, 1967;Loeb, 1966Loeb, , 1968Schonland and Collens, 1934;Raizer, 1991), which establishes the atmospheric ionized path to complete the lightning.…”
Section: Lightningmentioning
confidence: 99%
“…The first stage of lightning initiation was analyzed in [3][4][5][6][7][8][9][10][11][12][13]. Obviously, to initiate lightning, the field strength at least locally must be above the E br /P g , but the E/P g magnitudes measured in thunderclouds do not exceed 3-4 kV/cm/atm [14][15][16].…”
Section: Introductionmentioning
confidence: 99%